Development of a potentiometric mefenamate ion sensor for the determination of mefenamic acid in pharmaceuticals and human blood serum - Santini, A. O.; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Elsevier B.V., 2007)
The characteristics, performance, and application of a novel and simple electrode, namely Pt vertical bar Hg vertical bar Hg-2(MF)(2)vertical bar Graphite, where MF stands for mefenamate ion, are described. This electrode responds to MF with sensitivity of (58.9 +/- 0.7) mV decade(-1) over the range 1.0 x 10(-6) to 1.0 x 10(-2) mol L-1 at pH 6.0-9.0 and a detection limit of 6.2 x 10(-7) mol L-1. The electrode is easily constructed at a relatively low cost with fast response time (within 10-25 s) and can be used for a period of 4 months without significant change in its performance characteristics. The proposed sensor displayed good selectivity for mefenamate in the presence of several substances, especially concerning carboxylate and inorganic anions. The potentiometric sensor was successfully applied to the determination of mefenamic acid in pharmaceuticals and human serum samples. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mefenamate-sensitive electrode; potentiometry; pharmaceuticals; human blood serum